The Role of Simultaneous Interpretation in the System of Types of Translation - Daminov Navruz Kudratovich (Researchparks Publishing, 2022)
This article is devoted to the problems of classification of types of translation and, in particular, the place of simultaneous translation in them and its features. In the works of domestic and foreign scientists, various bases for classifying the types of translation are given. The purpose of the study is an attempt to clarify them and offer their own vision of this problem. Among other things, the authors emphasize the importance of taking into account the psychological factors that affect the activities of the translator, which determines the novelty of the work. Special attention is paid to the formation of stress resistance of translators to work in various situations of translation. In this regard, it is pointed out that it is promising to study the biofeedback method as a way to overcome the negative impact of stress in the process of translation.